2022
DOI: 10.1007/s00402-022-04403-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results after arthroscopic reconstruction of the posterolateral corner of the knee: A prospective randomized trial comparing two different surgical techniques

Abstract: Introduction Arthroscopic reconstruction techniques of the posterolateral corner (PLC) of the knee have been developed in recent years. Reconstruction techniques for higher-grade PLC injuries have not yet been validated in clinical studies. This study aimed to compare clinical outcomes of two different techniques and to present results of the first prospective randomized clinical trial of patients to undergo these novel procedures. Materials and methods 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 45 publications
1
40
1
Order By: Relevance
“…1 Reconstruction has demonstrated excellent clinical results with high Lysholm knee scores, high International Knee Documentation Committee subjective knee scores, and good range of motion postoperatively. 33,34 Various techniques-open versus all arthroscopic, nonanatomic versus anatomic (tibiofibular-based versus fibular-based), and autograft versus allograft have all been described for reconstruction. Arthroscopic techniques can produce biomechanically sound constructs.…”
Section: Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Reconstruction has demonstrated excellent clinical results with high Lysholm knee scores, high International Knee Documentation Committee subjective knee scores, and good range of motion postoperatively. 33,34 Various techniques-open versus all arthroscopic, nonanatomic versus anatomic (tibiofibular-based versus fibular-based), and autograft versus allograft have all been described for reconstruction. Arthroscopic techniques can produce biomechanically sound constructs.…”
Section: Reconstructionmentioning
confidence: 99%
“…Arthroscopic techniques can produce biomechanically sound constructs. Weiss et al 33 in their randomized controlled trial concluded that arthroscopic PLC reconstruction sufficiently restores posterolateral rotational, varus, and posterior drawer stability without neurovascular complications. Li et al 35 found that arthroscopic PT reconstruction demonstrated similar subjective and objective clinical outcomes compared with the open procedure.…”
Section: Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] In recent years, arthroscopic reconstruction techniques have been developed to provide stability while utilizing the bene ts of arthroscopic compared to open surgeries. [12,13] There are different types of reconstructive surgery depending on the type of injury-for example: arthroscopic popliteus tenodesis, bula-based anatomic PLC reconstruction (technique according to Arciero), arthroscopic-assisted anatomic PLC reconstruction, tibia and bula-based anatomic PLC reconstruction (technique according to LaPrade). [12] The LaPrade technique addresses the 3 primary stabilizing structures of the PLC: FCL, PLT, PFL.…”
Section: Introductionmentioning
confidence: 99%